The consequences of measurement error when estimating the impact of obesity on income - Donal O'Neill; Olive Sweetman (IZA Journal of Labor Economics, 2013)
This paper examines the consequences of using self-reported measures of BMI when estimating the effect of BMI on income for women using both Irish and US data. We find that self-reported BMI is subject to substantial measurement error and that this error deviates from classical measurement error. These errors cause the traditional least squares estimator to overestimate the relationship between BMI and income. We show that neither the conditional expectation estimator nor the instrumental variables approach adequately address the bias and briefly discuss alternative approaches that could be considered when faced with non-classical measurement error.
Keywords: C13; C26; I14; 330; obesity; non-classical measurement error; auxiliary data; instrumental variables; Körpergewicht; Statistischer Fehler; Irland